Pelvic Floor Muscle Training vs. Vaginal Vibration Cone Therapy for Postpartum Dyspareunia and Vaginal Laxity - Federico Villani; Izabella Petre; Florina Buleu; Stela Iurciuc; Luciana Marc; Adrian Apostol; Chiara Valentini; Elisabetta Donati; Tommaso Simoncini; Ion Petre; Cristian Furau (Medicina)
Background and Objectives: Pelvic floor dysfunction and sexual health issues are common postpartum due to weakened pelvic muscles, significantly impacting women’s quality of life (QoL). Pelvic floor muscle training (PFMT) is a widely used approach to address these issues. This study aimed to compare the effectiveness of two rehabilitation methods—vibrating vaginal cones (VCG) and PFMT exercises (CG)—in improving pelvic floor muscle strength, reducing dyspareunia, and enhancing sexual function in postpartum women. Materials and Methods: This 1-year retrospective observational analysis evaluated 57 postpartum women presenting with perineal muscle relaxation and sexual dysfunction. Participants were assessed 3 months postpartum (T0) and after 3 months of therapy (T1) at the Pelvic Floor Rehabilitation Clinic of Santa Chiara Hospital, Pisa. Outcomes were measured using the pubococcygeus (PC) test for pelvic floor strength and the Female Sexual Function Index (FSFI) for sexual function. Results: The results revealed significant improvements in pelvic floor muscle strength and sexual function across both groups. While both interventions effectively reduced dyspareunia, the VCG group demonstrated superior outcomes, with 96.67% of participants reporting no pain compared to 80.95% in the CG. FSFI scores improved significantly in both groups, with greater enhancements in arousal, desire, and pain domains observed in the VCG group (p < 0.01). Vaginal cone therapy also resulted in slightly higher gains in overall pelvic floor strength. Conclusions: These findings suggest that vibrating vaginal cones may be a promising option for postpartum pelvic floor rehabilitation, with potential benefits for improving sexual satisfaction and reducing pain.